Pengembangan Media Komik Digital Berbasis STEM untuk Meningkatkan Literasi Sains Siswa Sekolah Dasar - Tri Handayani (Direktorat Guru Pendidikan Dasar, Kemendikbudristek R.I., 2021)
The low motivation of students in increasing scientific literacy is evidenced by the low learning outcomes of grade VI students. This study aims to develop STEM-based digital comic media to improve students' scientific literacy skills, especially the dimensions of process, content, and context. This type of research is 4D research and development (Research & Development) through a descriptive approach. The development stages are Define, Design, Development, and Disseminate. Research during this pandemic was only carried out up to 3 stages of development. This research was validated by competent experts and teachers. Validation aspects include aspects of material feasibility, linguistic feasibility, and graphic feasibility. In terms of practicality, this media development uses 20 student responses and 1 teacher response. The use of tests in this study was only carried out to determine the cognitive improvement of students. Based on the validation results by 2 material experts, 2 media experts, and 2 graphic experts developing STEM-based digital comic media, the average score is 3.24, very feasible category with little input. The development of STEM-based digital comic media to improve student literacy skills in the dimensions of process, content, and context, it can be concluded that, for the three dimensional aspects, the average response is 97.85%, so that STEM-based digital comic media is categorized as very practical and the media is very feasible and practical. used for learning.